A Clean, Simple, and Efficient Synthesis of 2-Substituted Aryl (Indolyl) Kojic Acid Derivatives by Kaolin/Ag Nanocomposite as a Reusable Catalyst: A Green Protocol. (26th August 2013) - Sadeghi, Bahareh; Shahedi, Mohammad Reza
Abstract : Kaolin/Ag nanocomposite (kaolin/Ag nanocomposite) was synthesized in a nanoreactor by the calcination of the precursor at high temperature and was shown to efficiently catalyze the one-pot, three-component reaction of an aromatic aldehyde, kojic acid, and indole derivatives under solvent-free conditions to afford the corresponding 2-substituted aryl (indolyl) kojic acid derivatives in high yield.